2017
DOI: 10.1097/bot.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Translation, Cross-Cultural Adaptation, and Validation of the American Academy of Orthopaedic Surgeons Foot and Ankle Outcomes Questionnaire in Mexican-Americans With Traumatic Foot and Ankle Injuries

Abstract: We provide a Spanish translation and cross-cultural adaptation of the AAOS-FAOQ. The instrument demonstrates appropriate psychometric properties in Mexican-Americans with traumatic foot and ankle injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Following initial screening of the titles and abstracts, 353 records were excluded, leaving 24 articles for full text review. Following full-text review of the 24 articles, six articles were included in this review [3034] and details of the application of the eligibility criteria can be found in the PRISMA Diagram in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following initial screening of the titles and abstracts, 353 records were excluded, leaving 24 articles for full text review. Following full-text review of the 24 articles, six articles were included in this review [3034] and details of the application of the eligibility criteria can be found in the PRISMA Diagram in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…As Table 4 demonstrates, none of the articles included here scored higher than adequate on the methodological quality assessment checklist. Whilst several articles [3034] translated the PROM and then performed analyses of measurement properties on the translated PROM, these studies did not cross-culturally validate the translated PROMs using an analysis of measurement invariance. Therefore, it was not possible to determine any differences in scores secondary to cultural contextual factors and the box for cross-cultural validity was not deemed to be relevant in these instances.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations